Clinical Functional Profile of the Hands of Patients with Rheumatoid Arthritis at Royal Prima Hospital Medan - Coray Carolyn Ruth Pardede, Eifel; Alexander, Rico; Chiuman, Linda (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that frequently causes progressive joint damage, particularly in the hands, resulting in impaired functional ability in daily activities. This study aims to describe the hand function of patients with rheumatoid arthritis based on age, gender, and family history at Royal Prima Hospital Medan. This research employed a descriptive quantitative design with a cross-sectional approach involving 55 respondents who met the inclusion criteria. Data were collected using a structured hand function questionnaire assessing right hand, left-hand, and bilateral hand function across various activities. Data analysis was conducted using univariate and bivariate descriptive methods through cross tabulation. The results showed that hand function impairment was most prominent in patients aged >40 years, who predominantly fell into the “poor” function category. Female respondents demonstrated a higher level of functional limitation compared to males. Meanwhile, a family history of RAcontributed as a predisposing factor but did not directly correlate with the severity of functional impairment. Patients with a family history tended to fall within the “moderate” category, while more severe impairment was observed among those without a family history. Older age and female gender are major factors associated with reduced hand function in RA patients, whereas family history serves as a predisposition rather than a determinant of severity.